Gharar Problems in the Majek Tradition: Juridical Analysis of Farm Workers' Wages from the Perspective of Sharia Economic Law - Diningsih, Alfia; Jafar, Khumedi; Faizal, Liky; Rohmah Wati, Siti (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
The employment remuneration practices observed in the majek tradition in Semaka District, Tanggamus Regency reveal significant differences between customary law, the formal regulatory framework, and Sharia principles. The main issues identified in this examination include manifestations of legal ambiguity (gharar) and a lack of protection for workers' rights, stemming from unilateral decisions regarding remuneration and post-harvest wage determination. Data was obtained through comprehensive interviews with landowners and agricultural workers, then analysed through the lens of the principles of Fikih Muamalah and Maqashid Sharia. The findings indicate that the majek tradition fails to meet the legal criteria associated with ijarah contracts due to the prevalence of gharar fahish (excessive uncertainty) regarding wage amounts. Juridically and philosophically, this practice contradicts the principles of justice ('is) and property protection (hifz al-mal) as articulated in Shariah Maqashid. This study advocates the formalisation of direct employment contracts in written form to ensure legal certainty and the protection of agricultural workers, who are positioned as vulnerable parties (mustadh'afin).